Attenuation of ultraviolet irradiance in North European coastal waters - Niels K. Højerslev; Eyvind Aas (Oceanologia, 2001)
A total of 439 measurements of downward ultraviolet irradiance in North European coastal waters have been analysed, half of which have been taken from other authors. The depths Z(10%) where the irradiance is reduced to 10% of its surface value vary by one order of magnitude in the open coastal waters, both at wavelengths of 310 nm (0.3–10.4 m) and 380 nm (1.2–13.0 m). In the fjords and estuaries the depth ranges are reduced to 0.08–6.1 m at 310 nm and 0.18–7.7 m at 380 nm. Mixing with saline ocean waters can increase these light penetration depths to more than 10 m, while river water can reduce them to a few centimetres.